A pilot study linking reduced fronto–Striatal recruitment during reward processing to persistent bingeing following treatment for binge‐eating disorder. Issue 4 (12th October 2013) - Balodis, Iris M.; Grilo, Carlos M.; Kober, Hedy; Worhunsky, Patrick D.; White, Marney A.; Stevens, Michael C.; Pearlson, Godfrey D.; Potenza, Marc N.
ABSTRACT Objective The primary purpose of this study was to examine neurobiological underpinnings of reward processing that may relate to treatment outcome for binge‐eating disorder (BED). Method Prior to starting treatment, 19 obese persons seeking treatment for BED performed a monetary incentive delay task during functional magnetic resonance imaging (fMRI). Analyses examined how the neural correlates of reward processing related to binge‐eating status after 4‐months of treatment. Results Ten individuals continued to report binge‐eating (BEpost‐tx) following treatment and 9 individuals did not (NBEpost‐tx). The groups did not differ in body mass index. The BEpost‐tx group relative to the NBEpost‐tx group showed diminished recruitment of the ventral striatum and the inferior frontal gyrus during the anticipatory phase of reward processing and reduced activity in the medial prefrontal cortex during the outcome phase of reward processing. Discussion These results link brain reward circuitry to treatment outcome in BED and suggest that specific brain regions underlying reward processing may represent important therapeutic targets in BED. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:376–384)